The Barrier: A Novel - French, Allen, 1870-1946 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Barrier: A Novel" by Allen French is a work of fiction written in the early 20th century. The novel explores themes of ambition, social class, and personal relationships within a closely-knit community in New England. The narrative primarily revolves around Stephen F. Ellis, a business magnate who seeks recognition in the aristocratic circles of Stirling, and George Mather, a young entrepreneur who has recently faced a downfall. Their interactions, along with those of Judith Blanchard$1 (Ba strong and ambitious woman$1 (Bset the stage for a deeper exploration of societal dynamics and personal aspirations. At the start of the novel, the reader is introduced to the small city of Stirling, where excess and exclusivity define the lifestyle of its wealthy inhabitants. George Mather, a former president of the street-railway company, has just lost his position by a manipulative strike from his rival, Ellis. As Mather grapples with his defeat, he encounters Judith Blanchard, whose perceptions and ambitions bring additional complexity to his situation. The opening segments establish the contrasting aspirations of both men as well as Judith's growing awareness of her own desires, laying the groundwork for a narrative that promises to navigate the intricacies of love, power, and societal expectation. (This is an automatically generated summary.)s
Release date is 2013-01-06
E-text prepared by Fay Dunn, sp1nd, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: City and town life -- Fiction; Love stories; New England -- Social life and customs -- Fiction; Man-woman relationships -- Fiction; Social classes -- United States -- Fiction; Business -- Fiction